2022
DOI: 10.1002/2211-5463.13496
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TMEM160 leads to an increase in reactive oxygen species generation and the induction of the mitochondrial unfolded protein response

Abstract: Transmembrane protein 160 (TMEM160) was recently reported to be localized to the mitochondrial inner membrane, but mitochondrial function was noted to be unaffected by loss of TMEM160. In contrast to these previously published findings, we report here that the absence of TMEM160 influences intracellular responses. After confirming that TMEM160 is localized in the inner mitochondrial membrane, we knocked down TMEM160 in human cultured cells and analyzed the changes in cellular responses. TMEM160 depletion led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…13). A recent study 34 published during our research period has concurrently confirmed human TMEM160 to be mitochondrial, further validating the efficacy of CAT-S-guided mitochondrial discovery. These findings indicated the in situ profiling by CAT-S could also shed light on the hidden members of the mitochondrial proteome.…”
Section: "Mito Orphans" Discovered By Cat-ssupporting
confidence: 66%
“…13). A recent study 34 published during our research period has concurrently confirmed human TMEM160 to be mitochondrial, further validating the efficacy of CAT-S-guided mitochondrial discovery. These findings indicated the in situ profiling by CAT-S could also shed light on the hidden members of the mitochondrial proteome.…”
Section: "Mito Orphans" Discovered By Cat-ssupporting
confidence: 66%
“…Mitochondria are organelles of the cell respiratory system and provide ATP and ROS. Many studies have indicated that downregulation of TOMM20 could represent mitochondrial dysfunction and is often accompanied with increased oxidative stress ( Brown et al, 2019 ; Nhu et al, 2021 ; Yamashita et al, 2022 ). Oxidative stress is associated with various gynecological diseases, including adenomyosis ( de Carvalho et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…TMEM proteins are located in different biological membranes. For example, TMEM180 is in the plasma membrane ( 11 ), TMEM165 is in the late Golgi (trans) ( 12 ), and endoplasmic reticulum (ER) ( 13 ), TMEM74 and TMEM9 in the lysosome membrane ( 14 16 ), TMEM106A ( 17 ) and TMEM160 in the mitochondrial membrane ( 18 , 19 ), and TMEM48 in the nuclear membrane ( 20 ). For some TMEM proteins, their localization has been demonstrated experimentally for others, it has been predicted by bioinformatics tools ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%